2020
DOI: 10.1111/ppl.13191
|View full text |Cite
|
Sign up to set email alerts
|

Acetic acid improves drought acclimation in soybean: an integrative response of photosynthesis, osmoregulation, mineral uptake and antioxidant defense

Abstract: Exposure to drought stress negatively affects plant productivity and consequently threatens global food security. As global climates change, identifying solutions to increase the resilience of plants to drought is increasingly important. Several chemical treatments have recently emerged as promising techniques for various individual and combined abiotic stresses. This study shows compelling evidence on how acetic acid application promotes drought acclimation responses in soybean by investigating several morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 72 publications
12
32
0
Order By: Relevance
“…In the present study, drought exposure of lemon verbena plants induced a significant accumulation of H 2 O 2 , which was accompanied by a concomitant increment of MDA in the leaves at all levels of drought (Figure 3A,B). These results indicated that lemon verbena plants suffered from oxidative damage due to the negative consequences of drought at the cellular level, which is supported by previous reports in Glycine max and D. moldavica under water‐limited conditions (Kabiri et al, 2018; Rahman et al, 2020). In fact, a dynamic antioxidant system is a prerequisite for the elimination of ROS under abiotic stresses like drought (Rahman et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…In the present study, drought exposure of lemon verbena plants induced a significant accumulation of H 2 O 2 , which was accompanied by a concomitant increment of MDA in the leaves at all levels of drought (Figure 3A,B). These results indicated that lemon verbena plants suffered from oxidative damage due to the negative consequences of drought at the cellular level, which is supported by previous reports in Glycine max and D. moldavica under water‐limited conditions (Kabiri et al, 2018; Rahman et al, 2020). In fact, a dynamic antioxidant system is a prerequisite for the elimination of ROS under abiotic stresses like drought (Rahman et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…These results indicated that lemon verbena plants suffered from oxidative damage due to the negative consequences of drought at the cellular level, which is supported by previous reports in Glycine max and D. moldavica under water‐limited conditions (Kabiri et al, 2018; Rahman et al, 2020). In fact, a dynamic antioxidant system is a prerequisite for the elimination of ROS under abiotic stresses like drought (Rahman et al, 2020). However, the observed increased levels of H 2 O 2 and MDA, despite the increased activities of SOD, CAT and APX in the leaves of lemon verbena plants, indicated that the stimulation of the enzymatic system was not sufficient to cope with the excessive H 2 O 2 , and hence led to increased oxidative damage (Figure 3A‐E).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations